2017
DOI: 10.1111/jfd.12756
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gene expression in post‐smolt Atlantic salmon challenged by LF‐89‐like and EM‐90‐like Piscirickettsia salmonis isolates reveals differences in the immune response associated with pathogenicity

Abstract: Piscirickettsiosis is the main bacterial disease affecting the Chilean salmon farming industry and is responsible for high economic losses. The aim of this study was to describe and comparatively quantify the immune response of post-smolt Atlantic salmon infected by cohabitation with fish bearing LF-89-like and EM-90-like Piscirickettsia salmonis. The expression of 17 genes related to the immune response was studied in head kidney from cohabitant fish by RT-qPCR. Our results at the transcriptomic level suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 80 publications
3
34
0
Order By: Relevance
“…In the present study, the CD8α expression was downregulated and CD4-1 expression was upregulated in the spleen after challenge by both routes. This is in agreement with the results obtained in the study performed by Rozas-Serri, Peña, Arriagada, Enríquez, and Maldonado (2018). were found in highest frequency in fish vaccinated with the highest antigen dose (group A) at 2 wpc (i.p.…”
Section: Multiplex Immunoassaysupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, the CD8α expression was downregulated and CD4-1 expression was upregulated in the spleen after challenge by both routes. This is in agreement with the results obtained in the study performed by Rozas-Serri, Peña, Arriagada, Enríquez, and Maldonado (2018). were found in highest frequency in fish vaccinated with the highest antigen dose (group A) at 2 wpc (i.p.…”
Section: Multiplex Immunoassaysupporting
confidence: 93%
“…It has been described that P . salmonis is able to modulate cell‐mediated immunity and thus promoting intracellular replication of the bacteria and its survival inside the host cells (Rozas‐Serri et al, ). Thus, the acquired immune response developed in fish after vaccination against P .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, the expression of immunity genes evaluated indicated increments on il-1β , il-8 , and iκb-α genes during the 24 hpi, which later resulted in an increased cytotoxicity produced by the bacteria. Additionally, Rozas et al [ 77 ] reported an increase in the expression of il-1β , il-8 , tnf-α , and ifn-ɣ genes in the cohabiting fish kidneys at day 28 after being exposed to Trojan fish. It is important to mention that this finding was described in fish infected with both LF-89 and EM-90 strains, and the mortality in both groups began after the increment in the immune gene expression, between days 45 and 42 post challenge, respectively.…”
Section: Discussionmentioning
confidence: 99%